Features of the immunohistochemical diagnostics of neuroendocrine tumors. - Poslavs’ka, O. V. (Морфологія / Morphologia / Morfologìâ, 2015)
Background. The possibility of neuroendocrine tumor (NET) development from almost any organ causes problems in determination of a true primary site after detection of such metastases in lymph nodes or liver. It impels to consider the expression of immunohistochemical organ-specific markers such as cytokeratin (СК) along with the morphological characteristics. Objective. Determine the immunophenotype of neuroendocrine tumors of different localizations. Methods. Material from 52 patients (30 women and 22 men) aged 31 to 79 years (median 57 years) had been retrospectively analyzed during Jan 2012 – Oct 2014. Material included NET of different localization (9 cases in stomach, 7 in lung, 5 in colon, 3 in small intestine, 3 in larynx, 3 in mammary gland, 2 in pancreas, 1 in cervix and 1 in uterus body) or its metastasis from an unknown primary site (12 in lymph nodes, and 6 in the liver). СК Рan (clone AE1/AE3), Chromogranin A (CHR A) (clone LK2H10), Synaptophysin (SYN) (clone SYP02), CD95 (clone АВ3), CK 7 (clone OV-TL 12/30), Vimentin (VIM) (clone V9) were used as a primary monoclonal antibodies. Results. 96% of cases have turned out to be CK Рan+, except 2 (3.8%) NET with a localization in lymph nodes. 84.6 % of tumors expressed SYN, except 2 (22.2%) in stomach, 1 (14.3%) in lung, 1 (100%) in uterus body, 3 (25%) in lymph node and 1 (16.7%) in liver metastasis. 82.7% gave a positive staining for CHR A, except for 3 (60%) in colon, 1 (33.3%) in small intestine, 1 (11,1% ) in stomach , 3 (25 %) in lymph nodes metastases (both of which are NET with СК Рan-) and 1 (16.7%) of liver metastases. VIM+ were only 4 cases (both of which are NET, 1 (100% ) of uterus body and 1 (16.7% ) of liver metastasis). Positive cases of CK 7 expression were 6 (66.7%) in stomach NET (all carcinoids), 3 (42.9%) in lung, 1 (20%) in colon, 1 (33.3%) in larynx, 2 (16.7%) in lymph node and 2 (33.3%) in liver metastasis. Conclusions. The most common NET phenotype of these localizations is CK Рan+, CHR A+ and/or SYN+, CD95+, VIM-. Expression of CK 7 is intermittent and can not be used to reliably determine the primary site of NET.